Analyzing the role of entry level luxury products from the new luxury consumer perspective: a case study on the fine Jewelry market segment - Laera, Gianluca Cantori (2022)
The luxury industry is witnessing a major transformation pushed by the rise of the New Luxury Consumer. To build upon the scope of our CEMS Business Project, this paper focuses on understanding the role of entry-level products in the Fine jewelry market segment with respect to the New Luxury consumer. Through a thorough market analysis and semi-structured interviews with young consumers, we provide our view on the role held by these products and elaborate suggestions for luxury brands to develop entry-level product lines that satisfy the needs of these new consumers.